2018
DOI: 10.1016/j.peptides.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification and screening of potent antimicrobial peptides in arthropod genomes

Abstract: Using tBLASTn and BLASTp searches, we queried recently sequenced arthropod genomes and expressed sequence tags (ESTs) using a database of known arthropod cecropins, defensins, and attacins. We identified and synthesized 6 potential AMPs and screened them for antimicrobial activity. Using radial diffusion assays and microtiter antimicrobial assays, we assessed the in vitro antimicrobial effects of these peptides against several human pathogens including Gram-positive and Gram-negative bacteria and fungi. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The host immune modulation of parasite competition has been proposed in parasite–host interactive systems [ 51 , 52 ]. At least, for example, different numbers and families of antimicrobial peptide genes are encoded by different insects [ 53 ]. It was intriguing to find that the coinfection of ants or termites with M. anisopliae and the facultative saprophyte Aspergillus species largely resulted in the mycosis of insect cadavers by Aspergillus .…”
Section: Discussionmentioning
confidence: 99%
“…The host immune modulation of parasite competition has been proposed in parasite–host interactive systems [ 51 , 52 ]. At least, for example, different numbers and families of antimicrobial peptide genes are encoded by different insects [ 53 ]. It was intriguing to find that the coinfection of ants or termites with M. anisopliae and the facultative saprophyte Aspergillus species largely resulted in the mycosis of insect cadavers by Aspergillus .…”
Section: Discussionmentioning
confidence: 99%
“…We have found that DAN2 compromises the integrity of the bacterial membrane. Our in vitro study demonstrated that DAN2 does not lyse mammalian RBC which supports its potential use clinically [19]. Unlike bacterial cells which have 25% more anionic lipids that favor stronger electrostatic interaction, the mammalian cell membrane has large amounts of charge-neutral components, such as phosphatidylethanolamine, phosphatidylcholine, and sphingomyelin [29].…”
Section: Discussionmentioning
confidence: 88%
“…In our previous research, we have identified putative insect AMPs by searching newly sequenced arthropod genomes using known AMPs as homology templates [19]. We screened six cecropin and defensin derived peptides-DAN1, DAN2, HOLO1, LOUDEF1, INVICT1, and IXI for antimicrobial activity in vitro against several microbes including Gram-positive bacteria, Gram-negative bacteria and a single fungus.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy proved successful in this work, given that it identified 155 new putative HDP sequences from nine transcriptomes ( Supp Table S3 [online only ]). In contrast, an approach using similarity searches on deduced sequences derived genomic and expressed sequences tags (ESTs) from three insect species only identified six putative HDPs ( Duwadi et al 2018 ). One difference in these works is the presence of elements, such as introns and regulatory elements within the genomic sequences as they may limit the efficacy of gene identification by gene prediction methods.…”
Section: Resultsmentioning
confidence: 99%